COST Action 'ImpARAS': what have we learnt to improve food allergy risk assessment. A summary of a 4 year networking consortium. Issue 1 (18th May 2020) - Verhoeckx, Kitty; Lindholm Bøgh, Katrine; Constable, Anne; Epstein, Michelle M.; Hoffmann Sommergruber, Karin; Holzhauser, Thomas; Houben, Geert; Kuehn, Annette; Roggen, Erwin; O'Mahony, Liam; Remington, Ben; Crevel, René
Abstract: The growing world population and increased pressure on agricultural resources are driving a shortage of dietary protein sources. As a result, industry is developing more sustainable novel food protein sources such as insects, algae and duckweed and using new processing techniques. Consumer exposure to these novel or processed proteins, could cause new food allergies, exacerbating a public health issue which is already directly affecting an estimated 20 million Europeans. Introduction of novel foods should not add to the burden of food allergy and this calls for a reliable, harmonised, evidence‐based and validated allergenicity risk assessment strategy. The COST (Cooperation in Science and Technology) Action ImpARAS (Improved Allergenicity Risk Assessment Strategy), a four‐year networking project, identified gaps in current allergy risk assessment, and proposed new ideas and plans for improving it. Here, we report on the lessons learned from the ImpARAS network and suggestions for future research. The safe introduction of novel and more sustainable food protein sources, while protecting humans from food allergy, calls for a multidisciplinary approach based on an improved understanding of what determines the relative allergenic potency of proteins, novel testing and assessment methodologies, harmonized decision‐making criteria, and a clear ranking approach to express the allergenicity of novel product relative to that of existing known allergenic proteins: (from 'non'/to weakly and to strongly allergenic proteins).